Pemetaan Partisipatif dan Pengorganisasian Masyarakat Marginal dalam Reforma Agraria Perkotaan - Pradana, Nafisah; Ansori, Moh (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2025)
Urban agrarian reform faces serious challenges due to development pressures and unequal control over urban space, which disproportionately affect marginalized communities. Kampung Putat Jaya Baru RT 7 RW 11 in Surabaya is a densely populated settlement experiencing land tenure insecurity and vulnerability to eviction. This community service activity aims to enhance critical awareness and strengthen community solidarity in addressing urban agrarian issues through participatory mapping and community organizing. The method employed is Participatory Action Research (PAR), consisting of stages of observation, participatory problem identification, community based participatory mapping, collective reflection, and joint action planning. The results indicate that participatory mapping not only produces spatial maps and data of the settlement, but also serves as a collective learning process that shifts residents perspectives from being policy objects to becoming subjects who are aware of their rights to living space. This process increases residents’ awareness of their spatial conditions, strengthens community solidarity, and builds a social data foundation for advocacy. Therefore, participatory mapping has proven effective in empowering marginalized urban communities.